Aerogel dust-free waterproof facing material

Through the combination of modified silica aerogel and functional polymer, combined with the interface modification technology of silane coupling agent and nanotitanium dioxide, the problems of high hydrophilicity and insufficient water resistance of aerogel-based finishing materials are solved, and the water resistance, construction performance and long-term stability of the materials are significantly improved.

CN119822729APending Publication Date: 2025-04-15HEBEI JIANGGONG NEW BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510029370.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing aerogel finishing materials have difficult technical bottlenecks due to high hydrophilicity, insufficient water resistance, flying dust during construction, easy cracking or delamination of the coating.

Method used

Through the optimized combination of modified silica aerogel, functional polymer additives and other auxiliary materials, the interface modification technology of silane coupling agent and nanotitanium dioxide is used to form a dual structure of chemical crosslinking and physical network, which improves the water resistance, construction performance and long-term stability of the material.

Benefits of technology

It significantly improves the water resistance and aging resistance of the finishing materials, reduces the water absorption rate of the coating, enhances the hydrophobic properties and interface bonding of the materials, improves the dust-free and leveling properties of the construction, and extends the service life of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822729A_ABST
    Figure CN119822729A_ABST
Patent Text Reader

Abstract

The invention relates to the field of building materials, and discloses an aerogel dust-free waterproof facing material which comprises white cement, ash calcium powder, heavy calcium powder, modified silicon dioxide aerogel, latex powder, cellulose ether, white oil, bentonite, a functional polymer additive and the like. The hydrophobicity and the dispersity are enhanced. Through reasonable component proportion and optimized process, the water resistance, constructability and mechanical property of the material are remarkably improved, and the problems that an existing material is high in hydrophilicity, dust flies, a coating is prone to cracking and the like are solved. The material can be widely used for building interior and exterior wall facing, and has excellent performance and environmental protection property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to an aerogel dust-free and water-resistant finishing material. Background Art

[0002] Building finishing materials play an important functional and decorative role in modern construction projects, and their performance has a direct impact on the service life and appearance of buildings. With the improvement of people's requirements for the performance of building materials, especially the increasing requirements for water resistance, construction convenience and long-term use, various inorganic and organic composite materials have been widely used. However, some problems and shortcomings in the existing technology, especially in the application field of aerogel materials, still have difficult to overcome technical bottlenecks.

[0003] As a nanoporous structural material, aerogel has attracted attention for its excellent thermal insulation, light weight and low density, but its application in finishing materials still faces great challenges. In the prior art, the application of aerogel in finishing materials is limited due to its high hydrophilicity. The porous structure of aerogel easily leads to pore collapse after absorbing water, which not only weakens the water resistance of the material, but also may cause cracking and delamination of the material. In addition, the binding force between aerogel particles without surface modification and other matrix materials is weak, which may cause uneven dispersion of particles or detachment from the matrix during construction and long-term use, reducing the overall durability of the material. Although some studies have attempted to improve the interfacial properties of aerogel through surface modification technology, the existing modification methods are mostly limited to a single surface treatment (such as hydrophobic coating), and have failed to significantly improve the comprehensive performance of aerogel in finishing materials.

[0004] In terms of construction performance, the finishing materials in the prior art generally have problems of flying dust and inconvenient construction. Some inorganic powder materials (such as white cement and heavy calcium powder) will produce a lot of dust during the mixing and construction process, which not only affects the construction environment, but may also have adverse effects on the health of workers. Although existing technologies have attempted to improve the dust problem by adding organic thickeners or lubricants, they have not been able to fundamentally solve the dust pollution phenomenon during the construction process. In addition, the construction leveling and thixotropic properties of finishing materials are also key factors affecting the construction quality. Some materials in the prior art have insufficient fluidity or flow too fast during the construction process, which can easily cause uneven coating or sagging, increasing the difficulty of construction and rework costs.

[0005] On the other hand, the mechanical properties and long-term performance of building finishing materials are also key research directions in existing technologies. In high humidity, high temperature or hot and humid cycle environments, finishing materials often crack due to water absorption expansion or environmental stress, especially materials with uneven internal particle dispersion, which have a higher risk of cracking. Although some studies have introduced polymer latex powder to enhance the flexibility of finishing materials, the material's crack resistance and adhesion performance are still unsatisfactory due to insufficient addition of latex powder or failure to form effective synergy with inorganic materials. In addition, some inorganic materials may delaminate due to insufficient interfacial bonding during long-term use, further affecting the stability and durability of the coating.

[0006] Therefore, the present invention proposes an aerogel dust-free and water-resistant finishing material to solve the deficiencies of the prior art. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention provides an aerogel dust-free and water-resistant finishing material and a preparation method thereof, aiming to solve the problems of high hydrophilicity, insufficient water resistance, flying dust during construction, easy cracking or delamination of the coating, etc. of the prior art aerogel materials through an optimized combination of modified aerogel, functional polymer additives and other auxiliary materials, thereby significantly improving the water resistance, construction performance and long-term stability of the finishing material.

[0008] To achieve the above purpose, the present invention is implemented by the following technical scheme: aerogel dust-free and water-resistant finishing material, including the following components in a mass ratio range: White cement: 8-12 parts; As the main body of inorganic cementitious materials, white cement can provide high-strength substrate bonding ability and provide a basis for the hardening and structural stability of the material. Its high whiteness ensures the decorative effect of the finishing material and helps other ingredients to be evenly distributed.

[0009] White cement generates calcium hydroxide and calcium silicate hydrate (CSH) gel during the hydration reaction. The CSH gel has significant gelling ability and provides a uniform dispersion matrix for aerogel particles and other components.

[0010] Calcium powder: 10-15 parts; Calcium powder provides an alkaline environment, which makes it easier for other modifiers (such as functional polymer additives and latex powder) to form a cross-linked structure, thereby improving water resistance. At the same time, its chemical activity helps to enhance the bonding between the coating and the substrate.

[0011] Calcium hydroxide (Ca(OH)2), the main component of lime powder, releases hydroxide ions during the hydration reaction, reacting with the silane coupling agent and the active functional groups in the polymer network to further enhance the overall crosslinking density of the material.

[0012] Heavy calcium powder: 65-75 parts; Heavy calcium powder is used as the main filling material to increase the material's volume stability, crack resistance and wear resistance, while reducing the overall production cost.

[0013] The micron-sized particles of heavy calcium powder fill the gaps in the coating matrix, reducing the shrinkage and cracking that may occur in the material during the curing process, and together with the cementitious material form a dense structure to enhance the ability to resist water penetration.

[0014] White oil: 0.5-1.5 parts of white oil in the formula plays a role of construction lubrication, while reducing dust adhesion and improving the dust-free performance of the construction site.

[0015] White oil forms a hydrophobic film, covers the surface of material particles, reduces the electrostatic adsorption effect of dust particles, and thus achieves the purpose of dust-free construction.

[0016] Modified silica aerogel: 5-7 parts After being treated with silane coupling agent and nano-titanium dioxide, the modified silica aerogel has stronger hydrophobicity and structural stability. As the core component of the material, it gives the finishing material excellent water resistance and heat insulation.

[0017] The modified silica aerogel is chemically modified by silane coupling agent, and the surface active functional groups form chemical bonds with other components, thereby improving the interfacial bonding strength; nano-titanium dioxide further enhances the hydrophobic properties and improves the material's anti-pollution properties through photocatalytic effect.

[0018] Cellulose ether: 0.3-0.8 parts Cellulose ether acts as a thickener and water-retaining agent, which optimizes the construction performance of the material and makes the slurry have good thixotropy when applied.

[0019] Cellulose ether forms a stable physical network structure with water through its polymer chain structure, which improves the rheological properties and moisture retention capacity of the material, while slowing down water loss during the curing process and improving the uniformity of the material surface.

[0020] Latex powder: 0.8-2.0 parts Latex powder, as a polymer cross-linking component, improves the flexibility, adhesion and water resistance of finishing materials.

[0021] The latex powder forms a uniform polymer film during the construction process, which combines with the inorganic substrate to make up for the brittle defects of the inorganic material. At the same time, the polymer network further reduces the water absorption of the coating.

[0022] Starch ether: 0.02-0.1 parts Starch ether optimizes the workability of the material by reducing the viscosity of the slurry and improving the smoothness of the application.

[0023] Starch ether forms a polymer film after combining with water, which adjusts the rheological properties of the slurry and prevents sagging during the coating process.

[0024] Bentonite: 0.4-1.0 parts Bentonite provides the material with initial shaping ability and improves structural stability through its high water absorption and swelling properties.

[0025] Bentonite forms a physical gel network after absorbing water and swelling, which increases the thixotropy and anti-sagging ability of the slurry, and cooperates with other components to improve the mechanical properties of the material.

[0026] Functional polymer additives: 0.5-1.5 parts; Functional polymer additives further enhance the hydrophobicity and hydrolysis resistance of the coating through chemical cross-linking.

[0027] The active functional groups in the polymer form a dense three-dimensional network structure with the modified aerogel, latex powder and silane coupling agent through cross-linking reaction, which improves the overall water resistance and anti-aging properties.

[0028] Silane coupling agent: 0.05-0.2 parts; Silane coupling agents are used to enhance the interfacial bonding between inorganic materials and polymers.

[0029] Silane coupling agents chemically bond to the surface of inorganic materials through their active groups (such as silanol groups), while their organic groups are embedded in the polymer network, improving the interfacial bonding strength.

[0030] Nano titanium dioxide: 0.05-0.2 parts.

[0031] Nano-titanium dioxide gives the coating excellent hydrophobicity and UV resistance.

[0032] Nano-titanium dioxide significantly reduces water penetration by forming a dense coating on the surface of the material, and enhances the anti-pollution and anti-oxidation properties of the coating through its photocatalytic properties.

[0033] Preferably, the modified silica aerogel is modified by a silane coupling agent and nano-titanium dioxide.

[0034] Preferably, the functional polymer additive includes an aqueous polyurethane dispersion or a polyacrylate dispersion.

[0035] Preferably, the latex powder is ethylene-vinyl acetate copolymer latex powder or styrene-acrylate copolymer latex powder.

[0036] Preferably, the cellulose ether is methyl cellulose ether or hydroxypropyl methyl cellulose ether.

[0037] Preferably, the method for preparing the aerogel dust-free and water-resistant finishing material comprises the following steps: S1, prepare the modified silica aerogel and set it aside; S2, mix white cement, lime powder, heavy calcium powder and bentonite, and stir evenly; S3, mixing the latex powder, the functional polymer additive and deionized water, and stirring to form a solution; S4, adding modified silica aerogel, the solution obtained in step S3, cellulose ether, starch ether and white oil to the mixture obtained in step S2, stirring evenly, and standing for 8-12 hours; S5, re-stirring the material after standing to prepare the aerogel dust-free and water-resistant finishing material.

[0038] Preferably, the method for preparing the modified silica aerogel in step S1 comprises: (a) mixing the aerogel with a silane coupling agent and deionized water, and stirring for 1-2 hours; (b) adding nano titanium dioxide and continuing stirring for 30-60 minutes; (c) Drying the mixture at 60-80°C for 12-24 hours.

[0039] Preferably, in step S3, the mass ratio of the latex powder to the functional polymer additive is 1:1 to 1:3.

[0040] Preferably, the rotation speed of the stirring process in step S4 is 300-600 rpm, and the stirring time is 15-25 minutes.

[0041] Preferably, the re-stirring time in step S5 is 3-5 minutes, and the coating thickness during construction is 1-2 mm.

[0042] The present invention provides an aerogel dust-free and water-resistant finishing material. It has the following beneficial effects: 1. The present invention adopts the coordinated design of modified silica aerogel and functional polymer, combined with the interface modification technology of silane coupling agent, and effectively improves the water resistance and anti-aging performance of the finishing material through the dual structure of chemical crosslinking and physical network. The modified aerogel provides excellent hydrophobicity and nanoporous structure, and the functional polymer further enhances the density and stability of the material through crosslinking. Compared with the solution of using only polymer emulsion or traditional filler in the prior art, this technology greatly reduces the water absorption rate of the coating, so that the material maintains structural integrity in a long-term high-humidity environment, and solves the problems of high water absorption rate, poor water resistance and coating peeling after long-term use of existing materials.

[0043] 2. The present invention introduces silane coupling agent and nano-titanium dioxide to modify the surface of aerogel, which significantly improves the hydrophobicity, interfacial bonding and UV resistance of the material. The silane coupling agent achieves a strong interfacial bonding between the aerogel and the inorganic substrate through its active group, while the nano-titanium dioxide further improves the surface hydrophobicity of the material and increases the anti-pollution performance. Compared with the existing technical solutions of unmodified aerogel, the present invention overcomes the problems of poor dispersibility of aerogel particles and insufficient interfacial bonding, and effectively avoids the performance degradation caused by the collapse of aerogel pores. This technical innovation solves the shortcomings of the prior art, such as short service life and low durability caused by insufficient surface performance of aerogel.

[0044] 3. The present invention greatly optimizes the construction performance and dust-free effect of the material through the synergistic effect of white oil and cellulose ether. White oil forms a stable hydrophobic film in the material, which reduces the electrostatic adsorption of dust particles during the construction process and reduces the generation of dust at the construction site. Cellulose ether enhances the thixotropic properties of the slurry, so that the coating has better leveling and smoothness during the construction process. Compared with the problems of poor construction environment quality and uneven material application caused by dust pollution in the prior art, the technical solution of the present invention significantly improves construction safety and environmental adaptability, and solves the problems of unstable viscosity and serious sagging of traditional materials.

[0045] 4. The present invention improves the mechanical properties and durability of the material comprehensively through the reasonable ratio design of lime powder and bentonite, combined with the chemical dispersion and cross-linking of latex powder and functional polymer additives. The lime powder provides an alkaline environment for the matrix, the physical expansion properties of bentonite enhance the gelation and internal structural stability of the material, and the cross-linked network of latex powder and polymer further enhances the flexibility and crack resistance of the coating. Compared with the problem of easy cracking and insufficient durability of the material caused by the single use of inorganic fillers in the prior art, the coating of the present invention maintains the performance advantages of high strength and low cracking rate in long-term use, thereby overcoming the defects of traditional materials that crack or peel due to environmental stress. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The present invention is a flow chart of the preparation method of aerogel dust-free and water-resistant finishing material. DETAILED DESCRIPTION

[0047] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Please see attached Figure 1 : Example: Embodiment 1: Step 1: Preparation of modified silica aerogel Take 5 parts of silica aerogel, add 10 parts of deionized water, and stir for 30 minutes until evenly dispersed. Then add 0.1 parts of silane coupling agent and continue stirring for 1 hour to ensure sufficient grafting. Then slowly add 0.1 parts of nano titanium dioxide and stir at 300rpm for 45 minutes. Put the mixture into an oven, control the temperature at 65℃, and dry it for 18 hours to obtain modified silica aerogel particles.

[0049] Step 2: Mix the base powder Weigh 10 parts of white cement, 12 parts of lime powder, 70 parts of heavy calcium powder and 0.8 parts of bentonite, and pour them into a dry powder mixer. Set the stirring speed to 400 rpm and mix for 10 minutes until the powder is uniform.

[0050] Step 3: Functional solution preparation Add 1 part of latex powder and 1.5 parts of functional polymer additives into 15 parts of deionized water, and stir at 500 rpm for 5 minutes using a stirrer. The solution is homogeneous and ready for use.

[0051] Step 4: Slurry preparation Pour the powder mixture obtained in step 2 into a high-speed mixer and slowly add the solution in step 3. Then add 5 parts of modified silica aerogel particles prepared in step 1, 0.5 parts of white oil, 0.5 parts of cellulose ether and 0.05 parts of starch ether. Set the stirring rate to 500 rpm, mix for 20 minutes and then let stand for 10 hours.

[0052] Step 5: Usage and performance testing After standing, the slurry was stirred for 3 minutes and applied to the cement-based wall surface. The coating thickness was controlled at 1.5mm. After natural drying for 24 hours, the water absorption rate was tested. The test results showed that the water absorption rate of the material was 0.4%, which was significantly better than the unmodified material (water absorption rate was 5%). There were no cracks on the surface of the material, proving that both water resistance and construction performance were improved.

[0053] Embodiment 2: Step 1: Aerogel modification Weigh 6 parts of silica aerogel and mix with 15 parts of deionized water, stirring for 20 minutes. Add 0.15 parts of silane coupling agent, control the stirring speed at 400rpm, and continue for 1.5 hours. Then add 0.15 parts of nano titanium dioxide and stir at a low speed for 30 minutes. Put the mixture into a 70℃ oven and dry it for 24 hours to obtain modified silica aerogel.

[0054] Step 2: Dry powder mixing Weigh 11 parts of white cement, 10 parts of lime powder, 72 parts of heavy calcium powder and 1 part of bentonite. Pour the powder materials into a mixer, set the stirring speed to 300 rpm, and mix for 12 minutes until uniform.

[0055] Step 3: Solution preparation: 1.2 parts of latex powder and 1.8 parts of functional polymer additives were added to 10 parts of deionized water, and the mixture was rapidly stirred at 600 rpm for 5 minutes to obtain a uniform solution.

[0056] Step 4: Slurry preparation Pour the dry powder mixture of step 2 into the mixer, and slowly add the solution prepared in step 3 while stirring. Then add 6 parts of silica aerogel particles modified in step 1, 0.8 parts of white oil, 0.4 parts of cellulose ether and 0.08 parts of starch ether. Set the stirring speed to 400 rpm, stir for 25 minutes, and let stand for 12 hours.

[0057] Step 5: Construction Verification The material after standing was evenly applied on the surface of the gypsum-based wall, and the coating thickness was controlled to 1mm. During the construction process, on-site dust concentration monitoring showed that it was 70% less than that of traditional material construction. The coating surface was smooth and had no sagging, which verified the smoothness of the material's construction and dust-free performance.

[0058] Embodiment 3: Step 1: Modified silica aerogel preparation Weigh 7 parts of silica aerogel, add 20 parts of deionized water, and stir at 500 rpm for 40 minutes. Then add 0.2 parts of silane coupling agent, adjust the stirring rate to 300 rpm, and stir for 1 hour. Then add 0.2 parts of nano titanium dioxide and stir for 30 minutes. Put the mixture into an 80°C oven and dry it for 16 hours to obtain modified aerogel particles.

[0059] Step 2: Premixing of powder materials Take 12 parts of white cement, 15 parts of lime powder, 65 parts of heavy calcium powder and 1 part of bentonite. Put the powder materials into a dry mixer and stir for 10 minutes until they are evenly dispersed.

[0060] Step 3: Preparation of functional additive solution: Add 1 part of latex powder and 1.2 parts of functional polymer additive into 15 parts of deionized water, stir rapidly for 7 minutes, and the solution is completely dissolved.

[0061] Step 4: Slurry preparation Pour the dry powder from step 2 into a blender, gradually add the solution from step 3, and simultaneously add 7 parts of modified aerogel from step 1, 1.2 parts of white oil, 0.6 parts of cellulose ether, and 0.1 parts of starch ether. Stir at 600 rpm for 15 minutes and then let stand for 8 hours.

[0062] Step 5: Durability Test The prepared material was coated on the concrete base wall with a thickness of 2 mm. After the wet heat cycle test (humidity 90%, temperature 40°C, 100 cycles), no cracking occurred on the surface of the material, and the coating bonding strength retention rate reached 92%. Compared with traditional materials (strength retention rate of about 60%), the durability of the material of the present invention is significantly improved.

[0063] Comparative Example: Comparative Example 1: Comparative Example based on Example 1 (unmodified aerogel) Step 1: Use of unmodified aerogel 5 portions of unmodified silica aerogel were directly taken without surface treatment with silane coupling agent and nano-titanium dioxide for later use.

[0064] Step 2: Mixing of basic powders According to step 2 in Example 1, 10 parts of white cement, 12 parts of lime powder, 70 parts of heavy calcium powder and 0.8 parts of bentonite are taken and stirred for 10 minutes until uniform.

[0065] Step 3: Functional solution preparation Take 1 part of latex powder and 1.5 parts of functional polymer additives and add them to 15 parts of deionized water, and stir for 5 minutes until they are evenly dissolved.

[0066] Step 4: Slurry preparation Pour the powder mixture of step 2 into a high-speed mixer and slowly add the solution of step 3 while stirring. Then add unmodified silica aerogel (5 parts), 0.5 parts of white oil, 0.5 parts of cellulose ether and 0.05 parts of starch ether. Set the stirring rate to 500 rpm, stir for 20 minutes, and let it stand for 10 hours.

[0067] Note: This comparative example differs from Example 1 only in the surface modification of the aerogel, in that unmodified silica aerogel is used, and other steps and parameters remain the same.

[0068] Comparative Example 2: Comparative Example based on Example 2 (without adding white oil) Step 1: Aerogel modification Take 6 portions of silica aerogel and modify them in the manner of step 1 in Example 2, including adding a silane coupling agent, nano-titanium dioxide and performing drying.

[0069] Step 2: Mix the base powder According to step 2 in Example 2, 11 parts of white cement, 10 parts of lime powder, 72 parts of heavy calcium powder and 1 part of bentonite were weighed and stirred for 12 minutes until uniform.

[0070] Step 3: Functional solution preparation Take 1.2 parts of latex powder and 1.8 parts of functional polymer additives and add them to 10 parts of deionized water, and stir for 5 minutes until uniform.

[0071] Step 4: Slurry preparation Pour the powder mixture of step 2 into a mixer, and gradually add the solution of step 3. Then add modified aerogel particles (6 parts), 0.4 parts of cellulose ether and 0.08 parts of starch ether, but no white oil. Stir at a rate of 400 rpm for 25 minutes and let stand for 12 hours.

[0072] Comparative Example 3: Comparative Example based on Example 3 (without bentonite) Step 1: Aerogel modification According to step 1 in Example 3, 7 parts of silica aerogel were taken, modified with silane coupling agent and nano-titanium dioxide, and dried for later use.

[0073] Step 2: Premixing of powder materials Take 12 parts of white cement, 15 parts of lime powder and 65 parts of heavy calcium powder, omit the addition of bentonite, and directly carry out dry mixing operation with a mixing time of 10 minutes.

[0074] Step 3: Functional solution preparation Take 1 part of latex powder and 1.2 parts of functional polymer additives, add them to 15 parts of deionized water, and stir rapidly for 7 minutes until they are evenly dissolved.

[0075] Step 4: Slurry preparation Pour the powder mixture in step 2 into a blender and gradually add the solution in step 3. Then add 7 parts of modified silica aerogel, 1.2 parts of white oil, 0.6 parts of cellulose ether and 0.1 parts of starch ether. Stir at a speed of 600 rpm for 15 minutes and then let stand for 8 hours.

[0076] Comparative Example 4: Comparative Example based on Example 1 (reducing the amount of latex powder added) Step 1: Modified aerogel preparation According to step 1 in Example 1, 5 portions of silica aerogel were taken, modified with a silane coupling agent and nano-titanium dioxide, and dried for later use.

[0077] Step 2: Powder Mixing Take 10 parts of white cement, 12 parts of lime powder, 70 parts of heavy calcium powder and 0.8 parts of bentonite, and stir for 10 minutes until uniform.

[0078] Step 3: Functional solution preparation Take 0.5 parts of latex powder (half the amount in Example 1) and 1.5 parts of functional polymer additive, add them to 15 parts of deionized water, and stir for 5 minutes until they are uniformly dissolved.

[0079] Step 4: Slurry preparation Pour the powder mixture of step 2 into a high-speed mixer and gradually add the solution of step 3. Then add 5 parts of modified silica aerogel, 0.5 parts of white oil, 0.5 parts of cellulose ether and 0.05 parts of starch ether. Set the stirring rate to 500 rpm, stir for 20 minutes and then let stand for 10 hours.

[0080] Comparative Example 5: Comparative Example based on Example 3 (without aerogel modification) Step 1: Use of unmodified aerogel 7 portions of unmodified silica aerogel were taken for use without being treated with silane coupling agent and nano-titanium dioxide.

[0081] Step 2: Premixing of powder materials Take 12 parts of white cement, 15 parts of lime powder, 65 parts of heavy calcium powder and 1 part of bentonite, mix and stir for 10 minutes.

[0082] Step 3: Functional solution preparation Take 1 part of latex powder and 1.2 parts of functional polymer additives, add them to 15 parts of deionized water, and stir for 7 minutes until they are evenly dissolved.

[0083] Step 4: Slurry preparation Pour the powder mixture of step 2 into a blender, and gradually add the solution of step 3. Then add unmodified silica aerogel particles, 1.2 parts of white oil, 0.6 parts of cellulose ether and 0.1 parts of starch ether. Stir at a rate of 600 rpm for 15 minutes and let stand for 8 hours.

[0084] Test experiment: Experiment 1: Water resistance test Experimental Description Experimental objectives: The effect of the modified silica aerogel on improving the water resistance of the material was evaluated, and the advantage of the modified aerogel of the present invention in improving the water absorption resistance of the finishing material was verified.

[0085] Experimental materials and sample preparation: Example 1: Using modified silica aerogel, a sample was prepared according to the preparation method of Example 1.

[0086] Comparative Example 1: Unmodified silica aerogel was used, and other processes were consistent with Example 1.

[0087] Comparative Example 5: The aerogel was completely unmodified, no silane coupling agent and nano-titanium dioxide were added, and other formulation parameters were consistent with those in Example 1.

[0088] Experimental steps: Material coating: Each group of samples was evenly coated on the surface of cement-based specimens, with a coating thickness of 1.5 mm.

[0089] After coating, the specimens were dried naturally at room temperature for 24 hours.

[0090] Wet curing: The dried specimens were placed in a constant temperature and humidity chamber with the humidity set at 90% and the temperature set at 25°C for 7 days to ensure that the coating was fully cured.

[0091] Water absorption test: After curing, take out the specimens and record the dry mass.

[0092] Each group of test pieces was immersed in clean water for 24 hours, taken out and the surface moisture was quickly wiped off, and the mass after immersion was weighed.

[0093] Calculate the water absorption rate: water absorption rate = (mass after immersion in water - dry mass) / dry mass × 100%.

[0094] Surface observation: Compare the peeling conditions of the surface coatings of the three groups of specimens and record whether there are cracks or obvious peeling phenomena.

[0095] Experimental data: Table 1: Water resistance performance comparison test data sample Dry mass (g) Mass after immersion in water (g) Water absorption (%) Surface state Example 1 402.3 404.0 0.42 In good condition, no cracks Comparative Example 1 401.8 412.7 2.71 Slight peeling and cracks Comparative Example 5 403.5 416.2 3.14 Severe peeling and numerous cracks Modified aerogel plays a key role in the water resistance of the coating. Example 1 uses silane coupling agent and nano-titanium dioxide to modify the aerogel surface, forming a stable interfacial bonding force and avoiding structural collapse caused by water intrusion. Comparative Example 1 has not undergone surface modification, and the water absorption rate has increased significantly, proving that the unmodified aerogel has insufficient bonding force inside the material. In Comparative Example 5, since it is completely unmodified, the porous characteristics of the aerogel exacerbate water penetration, and the surface state deterioration is particularly obvious. This shows that surface modification technology is of great importance in improving the water absorption resistance of materials.

[0096] From the test results, it can be seen that the surface-modified aerogel particles not only form a tighter distribution in the material matrix, but also form effective chemical bonds with other components. This increased binding force blocks the path for water to enter the pores. In addition, the hydrophobicity of nano-titanium dioxide further enhances the waterproof performance of the coating. The comparison of the unadded samples shows that the lack of this additional effect weakens the overall water resistance. The present invention significantly improves the water resistance of the material through a dual mechanism - physical adsorption and chemical cross-linking.

[0097] It is worth noting that although the pore structure of the unmodified aerogel contributes to thermal insulation performance, its hydrophilicity leads to serious water absorption problems. After chemical modification with silane coupling agent, the surface properties of the aerogel are greatly improved, from hydrophilic to hydrophobic, making its distribution inside the material more uniform, enhancing the density and water resistance of the matrix. The difference in data shows that this modification technology does not just optimize a single performance of the material, but improves the durability and stability of the coating as a whole.

[0098] Experiment 2: Construction dust-free performance test Experimental Description Experimental objectives: The effect of white oil in reducing construction dust generation was evaluated, and the dust-free advantage of the present invention during the construction process was verified.

[0099] Experimental materials and sample preparation: Example 2: Aerogel facing material containing white oil. The sample is prepared according to Example 2.

[0100] Comparative Example 2: Aerogel finishing material without adding white oil, other components and processes remain the same.

[0101] Experimental steps: Confined Space Preparation: The experimental site is a 1 cubic meter closed space (length 1m × width 1m × height 1m), equipped with a dust concentration monitor (accuracy: ±0.01mg / m 3 ) and place it 20cm above the application area.

[0102] Before the experiment, clean the enclosed space to ensure that there is no background dust influence and the initial reading of the monitor is zero.

[0103] Materials and Construction: The materials of Example 2 and Comparative Example 2 were evenly applied to the surface of gypsum-based test pieces (size: 20 cm×20 cm×2 cm) using a scraper, and the coating thickness was controlled to be 1 mm.

[0104] In a confined space, each construction time is controlled to 60 seconds.

[0105] Dust concentration monitoring: Dust concentrations are monitored in real time during construction, with readings recorded every second.

[0106] Continue recording for 30 seconds after construction is completed until the dust concentration stabilizes, and take the peak values ​​during construction and after stabilization as the results.

[0107] Repeat the test: The operation was repeated three times for each group of samples, and the average value of the three tests was taken as the final result.

[0108] Experimental data: Table 2: Comparative experimental data of dust-free construction performance sample <![CDATA[First peak (mg / m 3 )]]> <![CDATA[Second peak (mg / m 3 )]]> <![CDATA[Third peak (mg / m 3 )]]> <![CDATA[Average value (mg / m 3 )]]> Example 2 0.19 0.22 0.18 0.20 Comparative Example 2 0.48 0.51 0.47 0.49 The addition of white oil significantly reduces the generation of dust during construction. This is not just a simple physical lubrication effect, it also forms a hydrophobic film on the surface of the material, which effectively reduces the friction between particles and reduces the amount of dust released. The dust concentration data in Example 2 is much lower than that in Comparative Example 2, indicating that the introduction of white oil plays an important role in dust-free performance. The dust peak in Comparative Example 2 is higher, reflecting that in the absence of white oil, a large number of particles are released into the environment due to friction and air disturbance during construction.

[0109] In addition, the role of white oil is not limited to reducing dust concentration. It also reduces the electrostatic adsorption behavior of fine dust particles by changing the affinity of the particle surface. This feature greatly shortens the time that the dust generated during the application process is suspended in the air. In the comparative data, the dust concentration of Example 2 decreases faster, which further verifies this point. This behavior is directly related to the hydrophobicity and lubricity of white oil from the perspective of the microscopic surface characteristics of the material.

[0110] It can be seen from the results that the generation of dust is not only related to the material composition, but also directly related to the bonding force between particles. White oil optimizes the internal distribution of the material through lubrication and dispersion effects, making it more uniform and smooth when scraping, and reducing the possibility of particles detaching from the matrix. Comparative Example 2 lacks this effect of white oil, and its friction coefficient between particles is larger, so more dust is released under the same operating conditions. These phenomena further illustrate that the technical breakthrough of the present invention in dust-free construction performance is the result of the dual mechanism of component optimization and physical lubrication.

[0111] Experiment 3: Coating mechanical properties test Experimental Description Experimental objectives: The role of bentonite in enhancing the mechanical properties (crack resistance and durability) of the coating was evaluated, and the coating stability and adhesion improvement effects of the present invention were verified.

[0112] Experimental materials and sample preparation: Example 3: Aerogel facing material containing bentonite. A sample was prepared according to the preparation method of Example 3.

[0113] Comparative Example 3: Aerogel facing material without bentonite, other components and preparation method are consistent with Example 3.

[0114] Experimental steps: Material coating: The materials of Example 3 and Comparative Example 3 were respectively and evenly coated on a concrete substrate with a substrate size of 15 cm×15 cm×2 cm, and the coating thickness was controlled to be 2 mm.

[0115] After coating, all test pieces were dried naturally under standard conditions (temperature 25° C., humidity 50%) for 24 hours.

[0116] Damp heat cycle test: The dried specimens were placed in a wet heat cycle test device, with the humidity set to 90% and the temperature set to 40°C, for a wet heat cycle test.

[0117] Each cycle lasted 24 hours and consisted of 12 hours of wetting (high humidity environment) and 12 hours of drying (low humidity environment).

[0118] After a total of 100 cycles of testing, the coating was taken out and the cracking conditions of the coating were recorded, including the number of cracks and the average crack length.

[0119] Pull-out strength test: Use a standard pull-out strength tester (ASTM C1583 standard), select three test points on the coating surface of the specimen, the pull-out speed is 50 N / s, and record the adhesion of the coating (unit: MPa).

[0120] The adhesion of each specimen was taken as the average value of three test points.

[0121] Crack observation and recording: A high-definition crack observation instrument (magnification: 20 times) was used to record the number and average length (unit: mm) of cracks on the coating surface of each specimen.

[0122] Experimental data Table 3: Comparative experimental data of coating mechanical properties sample Number of cracks Average crack length (mm) Tensile strength (MPa) Example 3 2 0.8 1.67 Comparative Example 3 6 2.4 0.94 The effect of bentonite in improving the mechanical properties of the coating is very obvious. The bentonite in Example 3 forms a stable physical gel network inside the coating through its high water absorption and swelling characteristics, which significantly reduces the risk of cracking of the coating during the wet heat cycle. In Comparative Example 3, no bentonite was added, and the number of cracks increased significantly, indicating that the internal structure of the material lacks sufficient stable support. The data after the wet heat cycle test also clearly show that bentonite not only enhances the crack resistance of the material, but also optimizes the long-term performance of the material under environmental stress.

[0123] As can be seen from the data, the difference in crack length also reflects the role of bentonite in the material microstructure. The crack length of embodiment 3 is shorter, indicating that the distribution of bentonite in the coating effectively disperses the external stress, and the stress concentration phenomenon is significantly weakened. On the other hand, in comparative example 3, the crack length is longer and the number is large, which is directly related to the lack of structural rigidity caused by the absence of bentonite. The material is prone to local stress concentration under stress, which leads to large-scale crack expansion.

[0124] The comparison of pull-out strength further verifies the bonding enhancement effect of bentonite. The physical expansion of bentonite fills the microscopic pores of the material and forms a tighter network structure with other components. This structure enhances the interfacial bonding between the coating and the substrate. In comparison, the pull-out strength of the specimen without bentonite is significantly lower. This shows that the present invention not only improves the mechanical properties of the coating by introducing bentonite, but also makes it show better durability in actual construction and long-term use.

[0125] Experiment 4: Flexibility and Adhesion Test Experimental Description Experimental objectives: The effect of the amount of latex powder added on the flexibility and adhesion properties of the material was evaluated to verify the effect of the optimization of the latex powder ratio in the present invention.

[0126] Experimental materials and sample preparation: Example 1: The amount of latex powder added is 1 part, and the sample is prepared according to the preparation method of Example 1.

[0127] Comparative Example 4: The amount of latex powder added was reduced to 0.5 parts, and other components and processes were consistent with Example 1.

[0128] Experimental steps: Material coating: The materials of Example 1 and Comparative Example 4 were respectively and evenly coated on a flexible plastic substrate with a substrate size of 20 cm×10 cm×1 mm, and the coating thickness was controlled to be 1.5 mm.

[0129] After coating, the coating was dried naturally for 24 hours under standard conditions (temperature 25°C, humidity 50%).

[0130] Flexibility test: The dried specimens were subjected to a 90° bending test at room temperature. The substrate was bent to 90° along the center line to observe whether cracks, peeling or delamination occurred on the coating surface.

[0131] Repeat the bending action 3 times and record the results of each test.

[0132] Adhesion test: Use a pull-out strength tester (ASTM C1583 standard), select three test points on the coating surface of the specimen, fix the pull-out fixture, gradually increase the pull-out force, and record the maximum pull-out strength (unit: MPa) when the coating is peeled off from the substrate.

[0133] The adhesion of each group of specimens was taken as the average value of three test points.

[0134] Experimental data: Table 4: Comparative experimental data of flexibility and adhesion The amount of latex powder added directly affects the flexibility and adhesion of the coating. In Example 1, the amount of latex powder added was 1 part, and the coating showed higher flexibility, and no cracks or peeling occurred after bending. In Comparative Example 4, the amount of latex powder added was reduced to 0.5 parts, and slight cracks appeared in the coating during the bending process, accompanied by local peeling. This difference clearly shows the key role of latex powder in the coating structure: its polymer film not only increases the flexibility of the coating, but also provides a stronger stress absorption capacity for the material. This characteristic is particularly important in construction and long-term use.

[0135] The pull-out strength data further verified the mechanism of action of latex powder. The higher latex powder content in Example 1 formed a uniformly distributed polymer network, which can effectively fill the microscopic pores of the material and form a stronger bonding force with the substrate surface. In Comparative Example 4, after the latex powder content was reduced, the interfacial bonding force between the coating and the substrate decreased, and the pull-out strength was significantly reduced. This shows that the integrity of the polymer network is indispensable in improving the adhesion of the coating.

[0136] The effect of latex powder is not only reflected in the mechanical properties of enhanced coating, but also optimizes the internal microstructure of the material. In the coating curing process, latex powder forms a continuous and stable polymer film through physical crosslinking and chemical bonding between molecules. This film plays an important role in the crack resistance, flexibility and bonding strength of the coating. Data comparison shows that the reasonable addition amount of latex powder is the key to achieve material performance balance. The optimized ratio in embodiment 1 not only overcomes the brittleness problem of traditional materials, but also provides more excellent long-term bonding performance for coating.

[0137] Experiment 5: Coating hydrophobicity test Experimental Description Experimental objectives: The effect of modified aerogel in improving the hydrophobic properties of coatings was verified, and the actual effect of the surface modification process was evaluated by comparing the hydrophobicity differences between modified and unmodified aerogels.

[0138] Experimental materials and sample preparation: Example 3: Modified silica aerogel. Samples were prepared according to the formula and process of Example 3.

[0139] Comparative Example 5: Unmodified silica aerogel, other formulas and processes are consistent with Example 3.

[0140] Experimental steps: Coating preparation: The materials of Example 3 and Comparative Example 5 were respectively evenly coated on the surface of a concrete substrate, the substrate size was 10 cm×10 cm, and the coating thickness was 2 mm.

[0141] After coating, dry naturally at room temperature for 24 hours.

[0142] Contact angle test: Using a contact angle meter, select three random points, drop 0.1 mL of deionized water on the coating surface, and measure the static contact angle of each water drop (unit: °).

[0143] Each specimen was tested three times and the average value was taken as the result.

[0144] Water drop angle test: Place the coated substrate on a flat plate with an adjustable tilt angle, starting from 0° and gradually increasing the tilt angle.

[0145] Add 0.1 mL of deionized water and record the inclination angle (unit: °) when the water drop starts to slide down.

[0146] Each specimen was tested three times and the average value was taken as the final result.

[0147] Experimental data: Table 5: Comparative experimental data of coating hydrophobicity The modified silica aerogel significantly enhances the hydrophobicity of the coating. The average contact angle of Example 3 reached 109.5°, far exceeding 80.8° of Comparative Example 5. This shows that the surface of the aerogel modified by silane coupling agent and nano-titanium dioxide changes from hydrophilic to hydrophobic, forming a molecular structure with anti-wetting ability. This surface modification not only changes the surface chemical properties of the aerogel particles, but also further improves its uniform dispersibility and interfacial bonding force in the coating. The unmodified aerogel exhibits a lower contact angle, indicating that its hydrophilicity makes it easier for water to infiltrate the coating surface, resulting in a significant decrease in hydrophobicity.

[0148] The comparison of the sliding angle further verifies the effect of the modified aerogel. The sliding angle of Example 3 is only 15.4°, while the sliding angle of Comparative Example 5 is as high as 32.7°, nearly doubled. This means that water droplets slide more easily on the surface of the modified aerogel coating, and the low adhesion of the coating surface is closely related to the hydrophobic properties of the aerogel. This property is directly derived from the surface modification of nano-titanium dioxide, which enhances the micro-roughness of the coating surface and reduces the contact area between the water droplets and the coating, thereby reducing the sliding resistance. The unmodified aerogel particles in Comparative Example 5, due to their hydrophilicity, hinder the movement of water droplets, and the sliding angle increases significantly.

[0149] From the perspective of material mechanism, the dual modification mechanism of modified aerogel is the core to achieve high hydrophobicity. Silane coupling agent changes the surface polarity of aerogel through chemical bonding, making it easier to fuse with the matrix material, while inhibiting the absorption of water in the pores. The addition of nano-titanium dioxide further enhances the stability and durability of the surface hydrophobic layer and prevents water droplets from penetrating into the micropores of the material. This modification process not only improves the performance of aerogel particles, but also optimizes the microstructure of the overall coating. In contrast, the unmodified coating exposes significant performance deficiencies, which fully demonstrates the technical innovation and practical value of the present invention in the hydrophobic performance of the coating.

[0150] Experiment 6: Construction leveling test Experimental Description Experimental objectives: Verify the effect of cellulose ether on coating construction performance (leveling and thixotropy), and evaluate the role of cellulose ether in material fluidity and molding stability.

[0151] Experimental materials and sample preparation: Example 2: The amount of cellulose ether added in the formula is 0.4 parts, and the sample is prepared according to the preparation method of Example 2.

[0152] Comparative Example 2: No cellulose ether was added, and other formulas and preparation methods were consistent with those in Example 2.

[0153] Experimental steps: Leveling time test: A glass substrate (size: 20 cm×20 cm) was placed on a horizontal table.

[0154] The materials of Example 2 and Comparative Example 2 were respectively coated on glass plates using a toothed scraper, with the tooth pitch of the scraper being 5 mm.

[0155] Use a stopwatch to record the time (in seconds) required from the completion of scraping to the complete disappearance of the tooth marks on the material surface.

[0156] Each material was tested 3 times and the average value was taken as the leveling time result.

[0157] Slump test: Prepare a standard slump cone (upper diameter: 5 cm, lower diameter: 10 cm, height: 15 cm), put the material into the cone, smooth the surface and quickly lift the cone.

[0158] Measure the maximum expansion diameter (unit: cm) of the material after it flows and record the data.

[0159] Each material was tested three times and the average value was taken as the slump test result.

[0160] Thixotropy observation: Stir the material in a mixer for 2 minutes, let it stand for 5 minutes, and observe whether the slurry has any sagging or stratification.

[0161] Preliminary characterization results of thixotropic properties were recorded.

[0162] Experimental data: Table 6: Construction leveling comparison test data The role of cellulose ether in improving the leveling and construction thixotropy of materials cannot be ignored. The leveling time of Example 2 is significantly shorter than that of Comparative Example 2, indicating that the addition of cellulose ether significantly reduces the surface tension of the material, allowing the slurry to quickly expand and fill the surface tooth marks after coating. Since no cellulose ether was added to Comparative Example 2, the leveling time was longer. This characteristic would lead to uneven material coating in actual construction and increase the probability of rework. The slump test results further revealed the difference in fluidity between the two groups of materials. The slump value of Example 2 was smaller, indicating that cellulose ether limited the excessive flow of the material through viscosity regulation, ensuring the uniform distribution of the slurry on the substrate.

[0163] Thixotropy is another important indicator of construction performance. No sagging or stratification was observed in the slurry of Example 2 after standing, while obvious stratification occurred in the slurry of Comparative Example 2 after standing. This phenomenon is closely related to the stabilizing effect of cellulose ether in the material. The polymer chain of cellulose ether can form a physical network with water molecules, which is evenly distributed during stirring and effectively prevents the sinking and stratification of slurry particles during standing. In Comparative Example 2, due to the lack of regulation of cellulose ether, the slurry particles lost the stability of uniform distribution, resulting in an increase in sagging.

[0164] From the material mechanism analysis, cellulose ether optimizes the construction performance of the coating by changing the rheological properties of the slurry. The hydrophilic groups in its molecular structure physically interact with other components in the slurry to form a temporary network structure, which not only ensures the fluidity of the slurry during the coating process, but also limits excessive flow after coating. This dynamic adjustment ability is the core of the optimization of leveling and thixotropic properties. Comparative Example 2 lacks this control mechanism and exhibits poor construction performance. Data comparison shows that the optimized ratio of cellulose ether of the present invention has significant advantages in construction efficiency and construction quality, providing more reliable performance support for practical applications.

[0165] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Aerogel dust-free and water-resistant finishing material, characterized in that: Includes the following mass ratio ranges: White cement: 8-12 parts; Calcium powder: 10-15 parts; Heavy calcium powder: 65-75 parts; White oil: 0.5-1.5 parts; Modified silica aerogel: 5-7 parts; Cellulose ether: 0.3-0.8 parts; Latex powder: 0.8-2.0 parts; Starch ether: 0.02-0.1 part; Bentonite: 0.4-1.0 parts; Functional polymer additives: 0.5-1.5 parts; Silane coupling agent: 0.05-0.2 parts; Nano titanium dioxide: 0.05-0.2 parts.

2. The aerogel dust-free and water-resistant finishing material according to claim 1, characterized in that: The modified silicon dioxide aerogel is modified by a silane coupling agent and nano titanium dioxide.

3. The aerogel dust-free and water-resistant finishing material according to claim 1, characterized in that: The functional polymer additive includes an aqueous polyurethane dispersion or a polyacrylate dispersion.

4. The aerogel dust-free and water-resistant finishing material according to claim 1, characterized in that: The latex powder is ethylene-vinyl acetate copolymer latex powder or styrene-acrylate copolymer latex powder.

5. The aerogel dust-free and water-resistant finishing material according to claim 1, characterized in that: The cellulose ether is methyl cellulose ether or hydroxypropyl methyl cellulose ether.

6. The method for preparing the aerogel dust-free and water-resistant finishing material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, prepare the modified silica aerogel and set it aside; S2, mix white cement, lime powder, heavy calcium powder and bentonite, and stir evenly; S3, mixing the latex powder, the functional polymer additive and deionized water, and stirring to form a solution; S4, adding modified silica aerogel, the solution obtained in step S3, cellulose ether, starch ether and white oil to the mixture obtained in step S2, stirring evenly, and standing for 8-12 hours; S5, re-stirring the material after standing to prepare the aerogel dust-free and water-resistant finishing material.

7. The method for preparing the aerogel dust-free and water-resistant finishing material according to claim 6, characterized in that: The method for preparing the modified silica aerogel in step S1 comprises: (a) mixing the aerogel with a silane coupling agent and deionized water and stirring for 1-2 hours; (b) adding nano titanium dioxide and continuing stirring for 30-60 minutes; (c) Drying the mixture at 60-80°C for 12-24 hours.

8. The method for preparing the aerogel dust-free and water-resistant finishing material according to claim 1, characterized in that: In step S3, the mass ratio of the latex powder to the functional polymer additive is 1:1 to 1:

3.

9. The method for preparing the aerogel dust-free and water-resistant finishing material according to claim 1, characterized in that: The rotation speed of the stirring process in step S4 is 300-600 rpm, and the stirring time is 15-25 minutes.

10. The method for preparing the aerogel dust-free and water-resistant finishing material according to claim 1, characterized in that: The re-stirring time in step S5 is 3-5 minutes, and the coating thickness during construction is 1-2 mm.